Does plant ecosystem thermoregulation occur? An extratropical assessment at different spatial and temporal scales. Issue 3 (10th December 2022) - Guo, Zhengfei; Still, Christopher J.; Lee, Calvin K. F.; Ryu, Youngryel; Blonder, Benjamin; Wang, Jing; Bonebrake, Timothy C.; Hughes, Alice; Li, Yan; Yeung, Henry C. H.; Zhang, Kun; Law, Ying Ki; et al.
Summary: To what degree plant ecosystems thermoregulate their canopy temperature ( T c ) is critical to assess ecosystems' metabolisms and resilience with climate change, but remains controversial, with opinions from no to moderate thermoregulation capability. With global datasets of T c, air temperature ( T a ), and other environmental and biotic variables from FLUXNET and satellites, we tested the 'limited homeothermy' hypothesis (indicated by T c & T a regression slope < 1 or T c  <  T a around midday) across global extratropics, including temporal and spatial dimensions. Across daily to weekly and monthly timescales, over 80% of sites/ecosystems have slopes ≥1 or T c  >  T a around midday, rejecting the above hypothesis. For those sites unsupporting the hypothesis, their T c – T a difference (Δ T ) exhibits considerable seasonality that shows negative, partial correlations with leaf area index, implying a certain degree of thermoregulation capability. Spatially, site‐mean Δ T exhibits larger variations than the slope indicator, suggesting Δ T is a more sensitive indicator for detecting thermoregulatory differences across biomes. Furthermore, this large spatial‐wide Δ T variation (0–6°C) is primarily explained by environmental variables (38%) and secondarily by biotic factors (15%). These results demonstrate diverse thermoregulation patterns across global extratropics, with most ecosystems negating the 'limited homeothermy' hypothesis, but their thermoregulation still occurs, implying that slope < 1 or T c  <  T a are not necessary conditions for plant thermoregulation. Abstract : See also the Commentary on this article by Drake, 238 : 921–923 .